Offline and computer‐based elearning interventions for medical students' education - Hervatis, Vasilis (2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The primary objective of this review is to assess the effects of offline, computer‐based eLearning compared with ‘traditional’ learning and other types of eLearning interventions for medical students’ knowledge as well as changes in skills and attitude towards the intervention. Additionally, as secondary objectives, this review will assess the economic impact (cost‐benefit, cost‐utility or cost‐effectiveness), unintended adverse effects, and medical students' satisfaction with using offline and computer‐based educational interventions.